Analisa Penyebab Penurunan Kinerja Cargo Oil Pump dan Seat Ring Valve Terhadap Kelancaran Discharge Cargo di Kapal Tanker - Ahmad Ndori; Susanto Susanto; Duchan Adief Achriyan (PPPM Polimarin, 2022)
The condition of the ship is very influential in one of the transportation. The results of field study observations on the ship MT. Dewayani, the authors found a cargo that could not be sucked in by the cargo oil pump (COP). This is due to a damaged valve seat ring. This study aims to determine the impact of the seat ring valve on the COP system, determine the factors causing the seat ring valve damage, and determine the role of the crew in maintaining the seat ring valve. The research method used is descriptive qualitative. Observations, interviews, literature studies, and documentation studies were conducted to collect data. The results of the study concluded that a damaged ring valve caused air to enter the COP system which had no bad impact. The cause of the seat ring valve damage is the lack of maintenance and the lack of professionalism of the crew, overrunning hours, and spare parts not according to the manual book. The role of the crew is to carry out maintenance according to PMS, operate according to the manual book, be calm and focused when there are problems, and cooperate between crew members.